Prosódia dos tipos frásicos em variedades do Português Europeu: produção e percepção - Cruz, Marisa (2017)
The present paper examines the intonational typology and tonal density of two varieties from central-southern European Portuguese (Alentejo – ALE and Algarve – ALG). The perception of sentence type and pragmatic meaning are also considered. Production data show that ALE, similarly to the Northern variety (NEP), presents more monotonal pitch accents and higher tonal density, whereas ALG seems to be halfway between the Standard (SEP) and the Northern varieties. Perception experiments show that declaratives produced by ALE and ALG speakers are easier to recognize by SEP listeners than interrogatives, and neutral sentences are more successfully perceived than focused ones.